Management of Human Resource Development on Education Quality Efforts in Pesantren Al-Muslimun Sumberagung Plason Magetan - Rahman Yurisya (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
Improvements to the quality of existing human resources in schools should receive more attention than the development of facilities and infrastructure. Because as written in Law No. 14 year 2005, that HRD is the most strategic factor in national education development and most decisive for the success of an educational institution. This research was conducted to find out how the implementation of human resource development management in an effort to improve the quality of education in Pesantren Al-Muslimun Sumberagung Plaosan Magetan, knowing how the role of human resource development management in improving the quality of education in Pesantren Al-Muslimun Sumberagung Plaosan Magetan, and knowing what factors which become supporters and obstacles in the implementation of human resource development management in Pesantren Al-Muslimun Sumberagung Plaosan Magetan. This research is field research with qualitative approach. The data are generated from interviews, observations, and documentation. While the steps of data analysis in this research with the process, data collection, data reduction, display data, take conclusions and verification. From the results of the research it is known that managerial and operational, the function of human resource management has been done in Pesantren al-Muslimun Sumberagung Plaosan Magetan and proved to play a very positive role. This can be seen in the process, implementation, and procedures in the stages of planning, management, employment, compensation, development and training, evaluation and dismissal. Although there are some light evaluation notes as well as a few inhibiting factors that should be solved and become the concern to be improved in the future. Keywords: Management, Resource Development, Education Quality, Improvement Efforts